Chemically Synthesized 58‐mer LysM Domain Binds Lipochitin Oligosaccharide. Issue 14 (26th August 2014) - Sørensen, Kasper K.; Simonsen, Jens B.; Maolanon, Nicolai N.; Stougaard, Jens; Jensen, Knud J.
Abstract Recognition of carbohydrates by proteins is a ubiquitous biochemical process. In legume–rhizobium symbiosis, lipochitin oligosaccharides, also referred to as nodulation (nod) factors, function as primary rhizobial signal molecules to trigger root nodule development. Perception of these signal molecules is receptor mediated, and nod factor receptor 5 (NFR5) from the model legume Lotus japonicus is predicted to contain three LysM domain binding sites. Here we studied the interactions between nod factor and each of the three NFR5 LysM domains, which were chemically synthesized. LysM domain variants (up to 58 amino acids) designed to optimize solubility were chemically assembled by solid‐phase peptide synthesis (SPPS) with microwave heating. Their interaction with nod factors and chitin oligosaccharides was studied by isothermal titration calorimetry and circular dichroism (CD) spectroscopy. LysM2 showed a change in folding upon nod factor binding, thus providing direct evidence that the LysM domain of NFR5 recognizes lipochitin oligosaccharides. These results clearly show that the L. japonicus LysM2 domain binds to the nod factor from Mesorhizobium loti, thereby causing a conformational change in the LysM2 domain. The preferential affinity for nod factors over chitin oligosaccharides was demonstrated by a newly developed glycan microarray. Besides the biological implications, our approach shows that carbohydrate binding to a small protein domain can be detected by CD spectroscopy.